Distance Learning Costs Based on General Cost Theory (Costos y Gestión, 2020)
Distance learning provides opportunities for individuals who can combine their education with their work.It also enables institutions to respond to a larger number of students and offer both hybrid courses and fulldistance options. The use of Internet in education has given rise to e-learning. Given the expected benefits itis necessary to identify and document the necessary resources for its development. The information on thecosts derived from e-learning projects development and supported by rigorous analysis is scarce. This workprovides a description of the required institutional resources for the development and delivery of coursesbased on e-learning and a cost analysis. The methodology for determining the cost factors is based on a literaturereview, and on experts’ interviews. The cost analysis is based on the General Cost Theory. As a result,it arises that labor costs has the greatest impact on the final result. It is expected that the detailed description of cost analysis would be useful for future assessments of this mode of education and constitute a supporttool for decision making in the field of high education.
Keywords: Distance Learning; E-Learning; Costs; High Education